Kolmogorov turbulence and information dissipation in molecular communication - Abbaszadeh, Mahmoud; Huang, Yu; Thomas, Peter J.; Wen, Miaowen; Ji, Fei; Guo, Weisi (IEEE, 2021)
Waterborne chemical plumes are studied as a paradigm for representing a means for molecular communication in a macro-scale system. Results from the theory of fluid turbulence are applied and interpreted in the context of molecular communication to characterize an information cascade, the information dissipation rate and the critical length scale below which information modulated onto the plume can no longer be decoded. The results show that the information dissipation decreases with increasing Reynolds number and that there exists a theoretical potential for encoding smaller information structures at higher Reynolds numbers.
Keywords: Molecular Communication; Turbulence; Small scales; Energy cascade; Information cascade